Trends and variability of monsoon and other rainfall seasons in Western Himalaya, India. (18th March 2014) - Singh, R. B.; Mal, Suraj
Abstract The local hydrological, agricultural and economic activities heavily depend on micro‐level rainfall. Therefore, this study examines trends and variability of rainfall in Uttarakhand state of western Himalaya, India. The season and station‐wise results of this study differ from India level results. The annual rainfall declined in high altitudes. Similarly, the monsoon rains declined in high altitudes and increased in low altitudes, whereas winter rainfall show mixed trends. The variability of monsoon rainfall was lowest for all stations and seasons, while the winters show low variability. Inter‐seasonal variability is recorded highest in plains and lowest in high altitudes.